Heroes of the surf : a rescue story based on true events - Carbone, Elisa Lynn (Viking, 2012)
When the huge steamship on which they are traveling runs aground off the New Jersey coast in 1882, two boys and their families are among the passengers dramatically rescued by members of the U.S. Life Saving Service. Includes notes about the event on which the story is based.